A Motivation Theory to Explain the Organizational Culture among Nurses in the Operating Room - Edy Purwanto; Nursalam Nursalam; Tintin Sukartini (Alta Dharma Publisher, 2020)
Organizational culture, as outlined in hospital policies regarding the culture of patient safety, should shape the caring behavior of health workers, especially nurses. Changes in the behavior of operating room nurses in the prevention of Surgical Site Infections (SSI) developed through organizational culture are unknown. The study aimed to explain the characteristics of organizational culture among in operating room. This study used a Cross-sectional descriptive to obtain the data of the characteristics of organizational culture in operating room nurses. We recruited 115 nurses in operating by using purposive sampling. The results showed the characteristic of organization culture-based, including 45.22% of the innovation and risk-taking was categorized as insufficient. Only 32.17% of participants have detail attention compared to the other two categories, and the orientation of the organization culture-based was 49.96%. Organizational culture of innovation and risk-taking, attention, and results orientation can improve the performance of nurses in the operating room and improve health services.